The Impact of Geopolitical Risks on Gold Prices: Empirical Evidence from the Israeli-Palestinian Conflict - Chahed, Kamar; Sadraoui, Tarek; Azouzi, Mohamed Ali (Journal of Posthumanism, 2025)
Geopolitical risks have long been recognized as important determinants of asset price movements, with gold historically regarded as a safe haven asset during periods of uncertainty. The Israeli-Palestinian conflict, which escalated on October 7, 2023, has intensified global geopolitical tensions, raising important questions about its impact on financial markets. This study investigates the influence of this conflict on gold prices, using daily data from two distinct periods, before the conflict, from January 1, 2023, to October 6, 2023, and during the conflict, from October 9, 2023, to September 30, 2024. By applying ARCH, GARCH, and EGARCH models, we aim to quantify the extent to which geopolitical instability affects gold prices. Our findings reveal a significant impact of the Israeli-Palestinian conflict on gold prices, reaffirming the role of gold as a safe haven asset amid geopolitical turbulence. These results contribute to the understanding of how geopolitical events influence different asset classes, providing valuable insights for investors and policymakers in managing risk and making informed investment decisions.